Determine if the two expressions are equivalent and explain your reasoning.
11p + 2(p + 3) and 1 + p(13) + 2
I WILL ONLY MARK BRAINLIEST IF YOU EXPLAIN
Answers
Answered by
2
Answer: No
Step-by-step explanation:
11p + 2(p+3) and 1+ (13p) +2
Combinethe terms of the first expression,
=11p + 2p + 6
=13p +6
Now combine the terms of the second expression,
=13p +3
So we find that these expressions are not equivalent.
Answered by
1
Answer:
Step-by-step explanation:
LHS = RHS
11p + 2p + 6 = 1 + 13p + 2
13p + 6 = 3 + 13p
LHS # RHS
Therefore, LHS is not equal to RHS so the answer is false, the two expressions are not equivalent.
Similar questions
Computer Science,
6 months ago
Science,
6 months ago
English,
1 year ago
Math,
1 year ago
English,
1 year ago